2019
DOI: 10.1159/000497440
|View full text |Cite
|
Sign up to set email alerts
|

Pediatric Brainstem Gliomas: A Retrospective Study of 180 Patients from the SEER Database

Abstract: Background/Aims: Large population-based studies are needed to assess the epidemiology and survival risk factors associated with pediatric brainstem gliomas. This retrospective study explores factors that may influence survival in this population. Methods: Utilizing the SEER database, the authors retrospectively assessed survival in histologically confirmed brainstem gliomas in patients aged 17 and younger. Survival was described with Kaplan-Meyer curves and multivariate regression analysis. Results: This analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
10
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 43 publications
2
10
0
2
Order By: Relevance
“…Patients with these tumors present with motor or sensory deficits, psychological symptoms, hydrocephalus and, rarely, seizures (24). In our series, the patients' presenting symptoms were headache, disequilibrium, ophthalmoplegia, dizziness, panic attack and absence seizures (16). Since sur-Immunohistochemical pathology results were consistent with grade 2 diffuse astrocytoma in 8 (50%) patients, and high grade diffuse glioma in 8 (50%) patients.…”
Section: Discussionsupporting
confidence: 48%
See 2 more Smart Citations
“…Patients with these tumors present with motor or sensory deficits, psychological symptoms, hydrocephalus and, rarely, seizures (24). In our series, the patients' presenting symptoms were headache, disequilibrium, ophthalmoplegia, dizziness, panic attack and absence seizures (16). Since sur-Immunohistochemical pathology results were consistent with grade 2 diffuse astrocytoma in 8 (50%) patients, and high grade diffuse glioma in 8 (50%) patients.…”
Section: Discussionsupporting
confidence: 48%
“…Deep seated midline gliomas originating from the brainstem constitute 10% of all primary brain tumors in the pediatric age group (16). The incidence of pediatric gliomas originating from the thalamus ranges between 1%-5% (2).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Diffuse brainstem pontine glioma (DIPG) is associated with dismal prognosis in both pediatric and adult patients, being highly infiltrative and less amenable to surgery (4,5). Pathologically, pediatric and adult patients with highgrade BSG (HGBSG), including World Health Organization (WHO) grades III and IV BSG, have worse clinical outcomes (6,7). Over the last two decades, we have gained deep understanding on pediatric DIPG and HGBSG in terms of biological characteristics, prognostic factors, and treatment strategies (8)(9)(10)(11).…”
Section: Introductionmentioning
confidence: 99%
“…Previously, studies have shown that malignant brainstem gliomas in pediatric patients have a poor prognosis. [10,11] Therefore, there is a need to discover a new complete prognostic scoring system for an accurate and useful prognosis assessment. A nomogram is a graphical representation of complex mathematical formulas.…”
Section: Discussionmentioning
confidence: 99%